2011
DOI: 10.1007/s10661-011-2111-x
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of some heavy metals in commercially important finfish and shellfish of the River Ganga

Abstract: Heavy metals are dangerous to aquatic organisms and it can be bioaccumulated in the food chain leading to diseases in human. Cumulative effects of metals or chronic poisoning may occur as a result of long-term exposure even to low concentrations. The accumulation of heavy metals varies depending upon the species, environmental conditions, and inhibitory processes. Concentrations of zinc, copper, lead, and cadmium were determined in finfish and shellfish species in the Gangetic delta using a PerkinElmer Sciex E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
2
26
1
Order By: Relevance
“…Moreover, the percentages of metals were significantly different (p < 0.05) in the soft tissues of clams from different sites. The results were in agreement with previous reports on the composition patterns of heavy metals in aquatic organisms (Sankar et al, 2006;Mitra et al, 2012;Tao et al, 2012), such as fish and shellfish. Because essential elements have an important role in the growth and development, immunity, reproduction, and other functions, aquatic organisms tend to accumulate relatively high levels of essential elements for normal life activities, but very high levels of the essential mineral elements will be harmful to the health of aquatic organisms and human beings (Gale et al, 2004).…”
supporting
confidence: 93%
“…Moreover, the percentages of metals were significantly different (p < 0.05) in the soft tissues of clams from different sites. The results were in agreement with previous reports on the composition patterns of heavy metals in aquatic organisms (Sankar et al, 2006;Mitra et al, 2012;Tao et al, 2012), such as fish and shellfish. Because essential elements have an important role in the growth and development, immunity, reproduction, and other functions, aquatic organisms tend to accumulate relatively high levels of essential elements for normal life activities, but very high levels of the essential mineral elements will be harmful to the health of aquatic organisms and human beings (Gale et al, 2004).…”
supporting
confidence: 93%
“…Their transfer into the food chain and results in their accumulation in the food stuffs which causes potential health risks to the consumers (Khan et al, 2008). Thus, it is important to determine their concentration in food stuffs and its amount transfer to the consumers during daily intake could be estimated by following formula (Wang et al, 2005;Mitra et al, 2012;Krishna et al, 2014.…”
Section: Human Health Risk Assessmentmentioning
confidence: 99%
“…It is evident that Zn 2+ binding directly mediates hydrophobic exposure of enzyme active site pocket and structural unfolding, as well as unfavorable aggregation in a broad variety of metallic/non-metallic enzymes, including creatine kinase and AK [21,22]. The roles of Zn 2+ in ocean invertebrates have not been well elucidated, but it has been found that Zn 2+ concentrations in the body of marine organisms, especially for marine invertebrates, are more excessive than other organisms’ metabolisms [23-25]. The reason of Zn 2+ can exist excess concentration in tissues of marine invertebrates is that it is prone to bind to macromolecules or present as insoluble metal inclusions in tissues [26].…”
Section: Introductionmentioning
confidence: 99%